Analisis Pengelolaan Keuangan Usaha Mikro Kecil dan Menengah (UMKM) Pada Usaha Gerabah di Desa Banyumulek - Sofiati Wardah; Agus Khazin Fauzi; Sigit Ary Wijayanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to find out and analyze how to manage finances, including budget planning, reporting, control, and control applied by the Association of Micro, Small and Medium Enterprises (UMKM) at the Pottery Business Association in Banyumulek Village. Data collection was carried out using a questionnaire to all members of the Banyumulek Pottery Association and samples for this study was 30 people. The results indicated that: (1) most of the respondents had not done budget planning as much as 53%; (2) most of the pottery craftsmen have not realized the use of the budget, namely 54%; (3) most of the craftsmen have not carried out the entire financial recording process, namely 62%; (4) most of the craftsmen have not done the financial reporting process, namely 54%; and (5) most of the craftsmen have not carried out the budget control process, namely 58%